Bibliometric Analysis of Research Productivity and Impact at the University of Dodoma: - Josephine Wilfred Ogondiek (International Journal of Librarianship (IJoL))
This study provides a bibliometric analysis of research publications from the University of Dodoma (UDOM) between 2007 and 2022, offering a comprehensive evaluation of the institution's scholarly output. By examining citation metrics and academic publications, the research reveals key patterns that shed light on the effectiveness and impact of UDOM's research initiatives. The study highlights significant authors and explores collaborative networks that contribute to enhancing research productivity. It also assesses how UDOM's research outputs contribute to its international ranking performance, serving as indicators of academic quality. Furthermore, the analysis underscores the university's commitment to both academic excellence and societal impact, demonstrating its alignment with global research standards and its broader role in advancing knowledge across diverse sectors.